Adapting T Cell Receptor Ligand Discrimination Capability via LAT - Lo, Wan-Lin; Weiss, Arthur (Frontiers in Immunology, 2021)
Self- and non-self ligand discrimination is a core principle underlying T cell-mediated immunity. Mature T cells can respond to a foreign peptide ligand presented by major histocompatibility complex molecules (pMHCs) on antigen presenting cells, on a background of continuously sensed self–pMHCs. How T cells can properly balance high sensitivity and high specificity to foreign pMHC, while surrounded by a sea of self-peptide ligands is not well understood. Such discrimination cannot be explained solely by the affinity parameters of T cell antigen receptor (TCR) and pMHC interaction. In this review, we will discuss how T cell ligand discrimination may be molecularly defined by events downstream of the TCR–pMHC interaction. We will discuss new evidence in support of the kinetic proofreading model of TCR ligand discrimination, and in particular how the kinetics of specific phosphorylation sites within the adaptor protein linker for activation of T cells (LAT) determine the outcome of TCR signaling. In addition, we will discuss emerging data regarding how some kinases, including ZAP-70 and LCK, may possess scaffolding functions to more efficiently direct their kinase activities.